Proposal for Growth and Development Evaluation Chart of Physical Abilities in Preschool Children -Analysis Based on Wavelet Interpolation Model-. (2022) - Fujii, Katsunori; Tanaka, Nozomi; Ishigaki, Tohru; Sakai, Toshiro
No abstract available